Dissenting Opinion of Corruption Court Judges as a Form of Freedom and Legal Reform in Indonesia - Simanjuntak, Louis Fernando; Rusmiati, Elis; Atmaja, Budi Arta (Corruptio, 2023)
The existence of dissenting opinions is a step in organizing law enforcement. This is also an important issue in organizing judicial power in relation to the 1945 Constitution and Law No. 48/2009 on Judicial Power. In Indonesia itself, judges are allowed to give dissenting opinions, although there has never been a clear definition of dissenting opinions. In Anglo-Saxon law, dissenting opinions have become commonplace, and these dissenting opinions often form new laws. This is in line with the term "judge made law". Therefore, the existence of dissenting opinion is very important, because it can continue to update the existing law.This research includes normative or doctrinal legal analysis because it wants an accurate and clear picture of the judge's dissenting opinion on the verdict of a corruption case. To explain and find answers to problems, theories are used as the basis for analysis, namely Legal Certainty Theory, Judicial Power Theory, Evidence Theory, Legal Construction Theory, and Sentencing Theory.The impact of the application of dissenting opinions by judges is an instrument towards a better quality of law enforcement, not just a matter of majority and minority in the consideration of judges but a consideration of whether or not a criminal offense has been proven. Therefore, further regulation of the conception of dissenting opinions in Indonesia is important. Legal reform of the Criminal Procedure Code in Indonesia and dissenting opinions must be regulated in the Criminal Procedure Code, precisely in the decree article 197, so that it becomes part of the consideration of a decision. The mechanism for entering dissenting opinions needs to be further regulated so that it becomes a form of transparency to the public.